2009
DOI: 10.1260/175682909789996168
|View full text |Cite
|
Sign up to set email alerts
|

Force Measurements and Flow Visualization for a Flexible Flapping Wing Mechanism

Abstract: This paper describes a series of experiments using a flapping wing mechanism. Force measurements were combined with high speed photography for two sets of flexible wings. The aerodynamic forces generated by flexible membrane type wings were measured using a two degree of freedom force balance constructed during the course of these experiments which measured the aerodynamic forces of lift and thrust. Lift and thrust measurements were acquired as the mechanism flapped the flexible wings for multiple cases, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For example, as shown in figure 22, Massey et al [130] adopted a PIV system to observe changes in the surrounding fluid of flexible and deformable flapping wings to understand their fluid dynamics. Deng et al [131] performed high-speed imaging to identify the deformation of a flexible flapping wing under vacuum conditions and in air.…”
Section: Devices For Visualizing Wing Deformation Effectsmentioning
confidence: 99%
“…For example, as shown in figure 22, Massey et al [130] adopted a PIV system to observe changes in the surrounding fluid of flexible and deformable flapping wings to understand their fluid dynamics. Deng et al [131] performed high-speed imaging to identify the deformation of a flexible flapping wing under vacuum conditions and in air.…”
Section: Devices For Visualizing Wing Deformation Effectsmentioning
confidence: 99%
“…One of the most noticeable effects of having a flexible wing was that the wing flexed such that the wingtip generally lagged the wing root (Massey et al, 2009). The schematic feature of the flexible wing motion has been displayed in the Fig.…”
Section: The Effects Of the Strut Pattern On The Flow Characteristicsmentioning
confidence: 99%
“…The studies reported by Weis-Fogh, 1 Lighthill, 2 Dickinson and G€ otz, 3 Wootton, 4 Dickinson, 5 Ellington et al, 6 Ellington, 7 Dickinson et al, 8 and Sun and Tang 9 were immense in contribution and laid a path to understand flapping flight. Hong and Altman, 10,11 Jardin et al, 12 Massey et al, 13 Krashanitsa et al, 14 Mazaheri and Ebrahimi, [15][16][17] Suryadi et al, 18 Jones and Babinsky, 19 Lua et al, 20 Ozen and Rockwell, 21 Curtis et al, 22 Granlund et al, 23 Goli et al, 24 and Lua et al 25 report various studies performed on flapping wings with an intention to visualize and understand the flow field behavior of heaving, pitching, and combined heaving-pitching of rigid airfoils, flat plates, and wings of low aspect ratio (AR).…”
Section: Introductionmentioning
confidence: 99%